Stress, Environment, Job Satisfaction and Employee Performance of Nepalese Enterprises - Devkota, Sruya Prasad; Rai, Bharat; Sharma, Bhanu Bhakta (Nepal Journal of Multidisciplinary Research, 2025)
Background: Worker job satisfaction is closely linked to productivity, influenced by psychological and physical workplace conditions. Factors such as workload, stress, and personal goals significantly impact job satisfaction, which, in turn, affects commitment, turnover rates, life satisfaction, and overall work performance. A supportive work environment enhances both satisfaction and productivity, whereas unfavorable conditions negatively impact them. Objective: This study explores the relationship between working conditions and productivity, focusing on motivation, job satisfaction, and the work environment in Nepal’s manufacturing industries. The research aims to identify effective workplace strategies that enhance employee performance and productivity. Methods: A survey was conducted among 500 workers across diverse industries in Nepal to examine occupational stress, work environment, and job performance. The study analyzed how various factors contribute to job satisfaction and productivity, particularly assessing the comparative impact of workplace conditions and stress levels. Findings: The results indicate that a positive work environment significantly enhances job satisfaction. Improvements in working conditions had a stronger influence on job satisfaction than merely reducing stress. Gender differences in job satisfaction were minimal, although women reported slightly higher satisfaction with income and personal development. Both work stress and the work environment had a substantial effect on job satisfaction and performance, with the work environment having a greater impact. Conclusion: The study highlights the importance of creating supportive work environments to improve employee performance. Organizations should implement strategies that foster workplace comfort, reduce stress, and provide continuous support. Encouraging meaningful professional relationships and ensuring a stress-free environment with well-suited staff contribute to higher job satisfaction and productivity. Novelty: This research offers insights into how businesses and future researchers can explore new conditions that enhance employee performance. By emphasizing the work environment's critical role, the study provides a foundation for designing policies that foster job satisfaction and productivity.